2010
DOI: 10.1111/j.1439-0388.2010.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

A robust method for simultaneous estimation of single gene and polygenic effects in dairy cows using externally estimated breeding values as prior information

Abstract: The aim of this study was to develop a robust method to estimate single gene and random polygenic animal effects simultaneously in a small field dataset with limited pedigree information. The new method was based on a Bayesian approach using additional prior information on the distribution of externally estimated breeding values. The field dataset consisted of 40,269 test-day records for milk performance traits for 1455 genotyped dairy cows for the 11 bp-deletion in the coding sequence of the myostatin gene. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
5
1
Order By: Relevance
“…Concerning additive effects, one copy of the "+" allele led to increases on milk, protein, and fat yields, the latter being significant (Table 4). These results are in good agreement with earlier studies (Buske et al, 2010). In the current study, important dominance effects were also observed for milk, fat, and protein yields, which were significant for fat and protein yields.…”
Section: Short Communicationsupporting
confidence: 83%
See 1 more Smart Citation
“…Concerning additive effects, one copy of the "+" allele led to increases on milk, protein, and fat yields, the latter being significant (Table 4). These results are in good agreement with earlier studies (Buske et al, 2010). In the current study, important dominance effects were also observed for milk, fat, and protein yields, which were significant for fat and protein yields.…”
Section: Short Communicationsupporting
confidence: 83%
“…Breeders of DP-BB make their selection decisions on the basis of the muscle hypertrophy mutation of the myostatin (MSTN) gene. Several recent studies (e.g., Buske et al, 2010 showed that the wild-type "+" allele of this gene is responsible for moderately higher milk, protein, and fat yields in DP-BB cows. It is also known that meat composition for fatty acids of Belgian Blue animals seems to be affected by muscle hypertrophy genotypes (Raes et al, 2001).…”
Section: Short Communicationmentioning
confidence: 99%
“…Allele substitution effects for one copy of the mh allele through all lactations were 276.06, 23.62 and 22.84 kg/lactation period (305 days) for milk, fat and protein yield, respectively. These values were lower than those found by Buske et al (2010) in a previous study using a Bayesian approach for only 1455 genotyped BBB cows. This difference might be explained by assumptions of this study, which included that allele substitution effects were the same across several breeds, which may not be accurate.…”
Section: Resultscontrasting
confidence: 53%
“…However, generally only few animals of a large population are genotyped for single genes of interest, making it difficult to estimate a single gene effect reliably (Gengler et al, 2008). This difficulty is more pronounced when data of genotyped animals are limited, unconnected or when the pedigree is incomplete (Buske et al, 2010). Genotyping more animals would be one solution, but this is costly or even unfeasible (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as an anonymous reviewer reported, the matrix G* −1 is very similar to the inverse of the matrix H used in the single-step genomic evaluations and included both pedigree-based relationships and differences between pedigree-based and genomic-based relationships (Aguilar et al, 2010;Christensen and Lund, 2010). In a different setting and after taking precautions to avoid double counting because of the use of the same data, regular genetic evaluation results from a larger population could also be used as external priors in gene effect discovery studies (e.g., Buske et al, 2010) or any other studies requiring accurate estimation of a polygenic effect jointly with marker, SNP, or gene effects.…”
Section: Resultsmentioning
confidence: 99%